Will vaccination against rotavirus infection with RIX4414 be cost-saving in Germany? - Stefanie Knoll; Christoph Mair; Ursula Benter; Katja Vouk; Baudouin Standaert (Health Economics Review, 2013)
Background: Rotavirus gastroenteritis (RVGE) is a frequent disease in young children. The recommended German paediatric immunisation schedule does not currently include rotavirus vaccination. A lack of economic data on the impact of routine vaccination is stated as one of the reasons. As a result, the current coverage rate is low, around 26%. This study investigated whether rotavirus vaccination using the two-dose rotavirus vaccine RIX4414 (Rotarix®, GlaxoSmithKline Vaccines) would be a cost-saving intervention from the perspective of the statutory health insurance (SHI) in Germany. Objective: The objective of the study was to analyse health outcomes (number of RVGE cases and hospitalisations prevented) and the associated cost to the SHI when comparing 100% rotavirus vaccination with no vaccination in Germany. Methods: A Markov cohort model simulated the number of RVGE events and related costs in a German birth cohort over the first 60 months of life with current disease management. The model compared an unvaccinated cohort with a fully vaccinated cohort. Vaccine efficacy data from international clinical trials were combined with German-specific epidemiological and cost data. Results were tested using extensive sensitivity analyses. Results: Full vaccination of a birth cohort against rotavirus disease would be expected to prevent 82% of RVGE cases, reducing RVGE frequency from 28 to 5 events per 100 children in the birth cohort up to age 5 years. The estimated cost reduction with vaccination for that period is predicted to be exteuro9.2 million with 100% coverage ( exteuro6.9 million with 75% coverage), mainly due to reductions in SHI reimbursement for productivity losses, hospital stays and visits to office-based physicians due to the vaccine's efficacy against severe disease. Conclusions: Routine rotavirus vaccination in Germany would reduce the number of hospitalised and outpatient cases. The associated investment could be fully offset by costs avoided in hospital stays, physician visits and SHI reimbursement of productivity losses. Sensitivity analysis indicated that vaccination would be cost-saving in 95% of simulations. Incremental cost was observed only under extreme conditions, especially when the time spent at home due to rotavirus disease was low or when vaccine efficacy against severe disease was heavily decreased.
Keywords: 330; Cost savings; Economic evaluation; Germany; Paediatric; RIX4414; Rotavirus; Vaccination